House of cards. The complete fourth season [videorecording (DVD)] - Spacey, Kevin; Wright, Robin, 1966-; Kelly, Michael, 1969- (Sony Pictures Home Entertainment, 2016)
They've always been a great team. But now, Frank and Claire become even greater adversaries as their marriage stumbles and their ambitions are at odds.